Concept maps to solve clinical cases as a teaching and learning strategy to be explored in nursing education: an essay - De Domenico, Edvane Birelo Lopes; Piconez, Stela Conceição Bertholo; Gutiérrez, Maria Gaby Rivero de (Online Brazilian Journal of Nursing, 2009)
The essay sustains the strategy of creating Concept Maps (CM) to solve clinical cases due to its strength to evidence the undergraduates’ cognitive processes regarding their capacity to generate effective responses when solving problems, a condition that is essential to clinical competence of nurses. Concept Maps are tools that can lead to changes in the way of teaching, evaluating, and learning. In addition, they promote significant learning and using CM to their complete potentiality implies to attribute new meanings to the concepts of teaching, learning, and evaluating.